Fire protection approaches in site plan review - Waseem, Mohammad Nabeel (CRC Press, 2016)
"The outcome of a fire review can greatly impact the internal fire and life safety features, as well as the architectural design of a building. An insider's guide for both novice and expert, Fire Protection Approaches in Site Plan Review provides the framework needed to design and evaluate a successful site plan for review. This book outlines the components of a fire review, provides fundamental knowledge of fire principles related to a review, and introduces concepts for site plan development that can reduce or eliminate the problems that take place during the review process and during fire emergencies. In addition to providing an overview of site plans, the author explains the items required for fire analysis, the kind of information that will be evaluated, and the items with which a reviewer should be familiar to begin a review. He also implements best practices, internationally recognized codes and standards, and applies real-life examples illustrating relevant ideas and concepts."--Back cover